Photoshop CS5 in easy steps - Shufflebotham, Robert (In Easy Steps Limited, 2010)
Provides information on the features of Adobe Photoshop CS5, covering such topics as opening and saving files, image and color basics, editing, layers, working with type, paths, channels and masks, and filters